Zheleznovodsk 2015: IRNRTU Design Department at the International Review Competition of Graduation Projects on Architecture and Design - Zheleznyak, Olga (project baikal, 2015)
The article presents the results of participation of the Design Department of Irkutsk National Research Technical University in the XXIVth International Review Competition of Graduation Works on Architecture and Design 2015 and in the International Competition of Scientific and Educational Literature. The Department submitted nine works. Eight of them received the 1st category diplomas of International Public Organization of Assistance to Architectural Education and a laureate diploma; one work was awarded with a 2nd category diploma.